PROBLEMS RELATED TO THE ECOLOGY AND SOME SOLUTIONS - Tukhtasinova Durdona Tolibjonovna (Journal of new century innovations, 2023)
Abstract: The present study delves into the pressing environmental issues that Uzbekistan is currently facing and examines potential solutions to address them.